2004
DOI: 10.1002/eji.200425139
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacilluscasei reduces CD8+ T cell‐mediated skin inflammation

Abstract: Probiotics, including Lactobacilli, have been postulated to alleviate allergic and inflammatory diseases, but evidence that they exert an anti-inflammatory effect by immune modulation of pathogenic T cell effectors is still lacking. The aim of this study was to examine whether L. casei could affect antigen-specific T cell-mediated skin inflammation. To this end, we used contact hypersensitivity to the hapten 2,4-dinitrofluorobenzene, a model of allergic contact dermatitis mediated by CD8 + CTL and controlled b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(119 citation statements)
references
References 51 publications
5
110
1
3
Order By: Relevance
“…For reduction of allergy, Matsuzaki et al (1998) reported that oral feeding of Lactobacillus casei strain Shirota effectively inhibited Immunoglobulin(Ig)E production both in vivo and in vitro. Besides stimulation of antibody production (Alvarez-Olmos and Oberhelman, 2001) and macrophage activity (Schiffrin et al, 1995), functional effects like inhibition of inflammation (Hart et al, 2003;Chapat et al, 2004), and autoimmune disorders (Gill and Guarner, 2004) were observed.…”
Section: Introductionmentioning
confidence: 99%
“…For reduction of allergy, Matsuzaki et al (1998) reported that oral feeding of Lactobacillus casei strain Shirota effectively inhibited Immunoglobulin(Ig)E production both in vivo and in vitro. Besides stimulation of antibody production (Alvarez-Olmos and Oberhelman, 2001) and macrophage activity (Schiffrin et al, 1995), functional effects like inhibition of inflammation (Hart et al, 2003;Chapat et al, 2004), and autoimmune disorders (Gill and Guarner, 2004) were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics could potentially reduce the incidence of VAP through various local and systemic effects that minimize colonization by more virulent species or optimize host immune defenses. These effects include reduced overgrowth of potentially pathogenic microorganisms, improved gut mucosal barrier function, reduced bacterial translocation, and toll-like receptormediated up-regulation of immune function (16)(17)(18)(19)(20)(21). Evidence supporting this theory is limited but promising (22).…”
mentioning
confidence: 99%
“…casei DN-114 001 were prepared at a stationary phase of growth as previously described (24). Mice (five to seven per group) were fed daily by gavage with 200 l of 10 8 CFU/ml L. casei DN 114 001 or 0.9% NaCl (control) from day 14 before colonic DNBS sensitization until the end of the experiments.…”
Section: Probiotic Treatmentmentioning
confidence: 99%
“…ϩ T cell-mediated skin contact hypersensitivity to 2,4-dinitro-1-fluorobenzene via a mechanism that required CD4 ϩ T cells (24). We thus asked whether the same L. casei treatment protocol could alleviate acute DNBS-specific CD8 colitis in BALB/c mice.…”
Section: Severity Of Cd8mentioning
confidence: 99%